Current management of stage IB2 and bulky IIA, locally advanced, and recurrent cervical carcinoma - Karen K. Lo; Anne O. Rodriguez; Janice Ryu; Vijay P. Khatri (Frontiers Media S.A., 2011)
Cervical cancer is one of the most common cancers affecting women, with most early disease treated with either surgery or radiation alone with an 85%-95% 5-year survival rate, while locally advanced cervical cancer (LACCA) requires multiple therapeutic modalities. The clear distinction between early and LACCA has, in recent years, blurred as stages IB2 and bulky IIA, which were traditionally thought of as early disease, have been shown to require more treatment than other early stage cervical cancer. LACC is now treated with cisplatin-based chemoradiation therapy based upon the results of the randomized co-operative group studies that demonstrated reduced relative risk of death, local failure rates, and incidence of distant metastases. Recurrent cervical cancer is devastating and is rarely cured. Treatment of recurrent cervical carcinoma depends on the previous therapy, the site of recurrence, and the extent of the recurrence. This review will outline the treatment options for the various stages of cervical cancer.